Cryptosporidium and Giardia lamblia Epidemiology in Middle Eastern Countries: study of the proliferation problem in the aquatic environment - Khan, Nadeem A.; El Morabet, Rachida; Khan, Roohul Abad; Bouhafa, Soufiane; Barhazi, Larbi; Sobyna, Vitaliy; Taraduda, Dmytro; Neklonskyi, Igor (Ecological Questions, 2021)
The aim is to present a summarized study of the available literature on Cryptosporidium and Giardia lamblia for Middle Eastern countries, in order to identify trends in human cryptosporidiosis and childhood morbidity, and to raise awareness among residents. This is necessary in order to address the gap in preventive measures required to mitigate the overall effect attributed to associated illness and its impact in the already water stressed Middle Eastern countries. To assess seroprevalence of Cryptosporidium and Giardia lamblia in Middle Eastern countries systematic review was carried out based on online articles published from 2010-2018. PubMed, Web of Science, Google Scholar, Science Direct, Scopus, World Bank and WHO report and scientific database were explored. The current study highlights the existing subsequent epidemiology, its seroprevalence distribution, genetic diversity across Middle Eastern countries since 2009. This study therefore will provide the platform for future research work and development in comprehending Cryptosporidium and Giardia lamblia epidemiology in Middle Eastern countries. It was found that lack of awareness, personal hygiene and sanitation facilities, poverty, indiscriminate eating habits are favourable infestation conditions for Cryptosporidium and Giardia lamblia infections. The prevalence for both Cryptosporidium and Giardia lamblia, is higher in developing countries as compared to developed countries. The originality is that it is the only study of its kind in the region, as such studies are still lacking in Middle East countries as compared to other European, Asian, American continents and countries.